Peran Negara Hukum Dan Tanggung Jawabnya Dalam Masyarakat Untuk Menjamin Kesejahteraan Dan Keadilan Di Indonesia - Anwar, Abdul Hijar; Aulia, Anastha Dilla; Arisma , Tasya Fazira; Putra , Roni Masa (Journal of Global Legal Review, 2024)
This article discusses the role of the rule of law in ensuring welfare and justice in Indonesia, as well as the responsibilities carried by the state in the context of society. The purpose of this study is to analyze how the principles of the rule of law can be implemented to achieve social welfare and justice for all citizens. The method used is empirical juridical with a qualitative approach with case study analysis and interviews with various stakeholders, including academics, legal practitioners, and civil society. The results of the study indicate that although there is a supporting legal framework, there are still many challenges in implementation, including corruption, discrimination, and unfair access to public services. It was found that a strong commitment from the state, collaboration with the community, and transparency in the decision-making process are the keys to realizing true welfare and justice. This article is expected to contribute to thinking in developing fairer and more effective public policies in Indonesia.